Analisis Bibliometrik terhadap Likert Scale Mathematics Berbasis VOSViewer - Nikita Dewi; Joko Soebagyo (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
This bibliometric analysis focuses on publications related to the Likert scale using VOSViewer based on Google Scholar data. This study was conducted to determine the number of international publications on the trend of research development using a Likert scale in the time interval between years 0-0. The data search was carried out using the PoP (Publish or Perish) software based on Google Scholar with the keywords Likert Scale Mathematics. The data is in the form of journals with a sample of 1000 journals. Then the data were analyzed using VOSViewer and Ms Excel. The results showed that the number of research publications related to Likert scale mathematics experienced an unstable situation where the most publications occurred in the 2012-2016 interval, namely as many as 246 article titles. The publishers who publish the most scientific journals are Elsevier, Springer, Taylor & Francis, and Wiley Online Library. Likert scale mathematics research with a fairly high density, namely the Likert scale, the rest has a low density such as validation, engineering, mathematics performance so that it is possible to be used as a theme for the next research.